PENERAPAN KONSEP RESTORATIVE JUSTICE PADA TINDAK PIDANA ANAK PERSPEKTIF HUKUM ISLAM DAN HUKUM PROGRESIF - Sodik, Fazar (Strata Law Review, 2024)
Restorative justice is an alternative concept for resolving criminal cases committed by minors or teenagers who cannot be said to meet the requirements to serve sentences equivalent to adults. By prioritizing the restoration of the victim's and perpetrator's conditions to reconcile both parties, while in Islamic law with the concept of qisas-diyat compensation, as-sulhu conciliation, and forgiveness between the perpetrator and the victim, this thesis will discuss the correlation and review of Islamic law and progressive law in the application of restorative justice in child criminal offenses. This research aims to answer the questions that formulate the problem how is the concept of restorative justice in the juvenile criminal justice system from the perspective of Islamic law and progressive law? This study uses a qualitative method with library or literature research: descriptive analysis. This study's results show that applying the restorative justice concept has several methods, including a reconciliation approach, a forgiveness approach, an apology approach, and a sincere remorse approach. Meanwhile, in Islamic law, this form of restorative justice can be in the form of compensation with the concept of qisas-diyat, conciliation in Islam with the concept of as-sulhu in the implementation of Islamic criminal law with the application of ta'zir, and al-afwu forgiveness. The application of Restorative justice in child criminal acts from a progressive legal perspective is manifested in the form of diversion.